2014
DOI: 10.1080/02791072.2014.920118
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana, Expectancies, and Post-Traumatic Stress Symptoms: A Preliminary Investigation

Abstract: Previous work suggests that people might turn to marijuana to alleviate the symptoms of post-traumatic stress disorder (PTSD) and associated distress. Expectancy theories emphasize that the use of drugs correlates with their anticipated effects. The current study examined multivariate links among marijuana use, PTSD symptoms, and expectancies for marijuana-induced changes in those symptoms. Over 650 combat-exposed, male veterans who used marijuana at least once per week completed measures of PTSD symptoms, mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Moreover, when an individual meets PTSD criteria and concurrently uses cannabis, they typically experience increased withdrawal and craving [8]. Other studies either show mixed support for both the potential harms [26,62,104,148], the therapeutic benefits, of which mostly involves improvements in sleep-related outcomes [18,45,64,124], or show lack of association between PTSD outcomes and cannabis use [80]. There is mixed data for the use of cannabis as a therapeutic treatment for PTSD.…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when an individual meets PTSD criteria and concurrently uses cannabis, they typically experience increased withdrawal and craving [8]. Other studies either show mixed support for both the potential harms [26,62,104,148], the therapeutic benefits, of which mostly involves improvements in sleep-related outcomes [18,45,64,124], or show lack of association between PTSD outcomes and cannabis use [80]. There is mixed data for the use of cannabis as a therapeutic treatment for PTSD.…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…Another study examined the administration of THC in patients with PTSD, describing favourable results in a sample of 10 participants [124]. To note, nearly half of the studies that assess cannabis use in PTSD, as well as its potential therapeutic effects, were conducted in U.S. military veterans, who exhibit high comorbidities of cannabis use and CUD, commonly reporting the use of cannabis to cope with one's traumatic experiences [8,45,62,78,80,98,104,105,153]. This population may be the most benefited by research in this area based on the high prevalence of cannabis use, which may have positive or negative effects on recovery.…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…Two veteran studies have shown that cannabis expectancies about anticipated benefits of cannabis use, a construct conceptually related to motives (Cox & Klinger, 1988), mediated the relation between symptoms of PTSD and cannabis use in an internet survey of combat veterans (Earleywine & Bolles, 2014), and the relation between depressive symptoms and cannabis use among cannabis dependent military veterans (Farris et al, 2014). Other work suggests the remission of PTSD symptoms is associated with a 75% or greater reduction in drug and alcohol use days, but reduction in SUD symptoms does not improve PTSD symptoms (Hien et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first novel aim was to concurrently examine the relative roles of PTSD and MDD on multiple indicators of cannabis use including cannabis use frequency, cannabis-related problems, and diagnosis with past 12-month DSM-5 CUD. Based on prior work (e.g., Boden et al, 2013;; Earleywine & Bolles, 2014; Farris et al, 2014), we hypothesized that each affective disorder will be significantly associated with each of the three cannabis use indices. The hypotheses pertaining to the strength of the association of PTSD relative to MDD with the cannabis outcomes were exploratory given these predictors have not been previously examined concurrently in one comprehensive study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation